Design of complex w/o/w emulsion for salt reduction in food emulsions - Zhang, L (2021)
The strategy of reducing salt levels in high-moisture foods by using water-in-oil-in-water (w/o/w) double emulsions has generated significant interest in recent years, due to the features of both encapsulation and controlled delivery of double emulsions.